Time-dependent effects of tumor necrosis factor α on Ca2+-dependent secretion in murine small intestinal organoids - Pauer, Svenja Mareike; Buß, Brigitta; Diener, Martin; Ballout, Jasmin (Frontiers in Physiology, 2024)
Background: Intestinal organoids are stem cell-derived, 3D "mini-guts" with similar functions as the native intestinal epithelium, such as electrolyte transport or establishment of an epithelial barrier. During intestinal inflammation, epithelial functions are dysregulated by proinflammatory cytokines like tumor necrosis factor α (TNFα) and other messengers from the immune system resulting in a loss of electrolytes and water due to an impaired epithelial barrier and higher net secretion.Methods: A murine small intestinal organoid model was established to study (long-term) effects of TNFα on the intestinal epithelium in vitro using live imaging, immunohistochemical staining and qPCR.Results: TNFα induced apoptosis in intestinal organoids as indicated by an increased number of cells with immunoreactivity for cleaved caspase 3. Furthermore, TNFα exposure led to swelling of the organoids which was inhibited by bumetanide and was concomitant with an upregulation of the bumetanide-sensitive Na + -K + -2Cl -symporter 1 (NKCC1) as shown by qPCR. Fura-2 imaging experiments revealed time-dependent changes in Ca 2+ signaling consisting of a rise in the basal cytosolic Ca 2+ concentration at day 1 and an increase of the carbachol-induced Ca 2+ response after 3 d TNFα exposure. This was prevented by preincubation with La 3+ , an inhibitor of non-selective cation channels, or by using a Ca 2+ -free buffer indicating an enhancement of the Ca 2+ influx from the extracellular side by the cytokine. No significant changes in cDNA levels of epithelial barrier proteins could be observed in the presence of TNFα.Intestinal organoids are a useful tool to study the mechanism underlying the TNFαinduced secretion on enterocytes such as the regulation of NKCC1 expression or the modulation of cellular Ca 2+ signaling.